CINEMATOGRAPHY IN GABRIELE MUCCINO’S THE PURSUIT OF HAPPINESS (2006) - Hendrajat, Sulthan Bonang; Priyawan, Pepen; Sudarisman, Yoga (Universitas Islam Negeri Sunan Gunung Djati, 2023)
This study aimed to study cinematography elements presented in Gabriele Muccino’s The Pursuit of Happiness (2006). To analyse the object of the research, it used cinematography theory by Blain Brown. The study used descriptive qualitative research design. Drama genre is one of the biggest and popular genre in the movie industry, since it shares some empathy, hopes, aspirations, dreams and fears (Editors, 2018). It focused on analysing the dramatic aspect through cinematography using Gabriele Muccino’s The Pursuit of Happiness (2006) movie. The study found that many cinematography elements in Gabriele Muccino’s The Pursuit of Happiness (2006) are proven using dramatic aspect from both lighting and camera technique. In conclusion, the movie shows a drama genre movie which has cinematography elements that need to be added to deliver the emotion of the story and to increase dramatic elements in the movie. Keywords: cinematography, genre, drama